Analysis of Hepatitis B Virus Genotype D in Greenland Suggests the Presence of a Novel Quasi-Subgenotype - de Bernardi Schneider, Adriano; Osiowy, Carla; Hostager, Reilly; Krarup, Henrik; Børresen, Malene; Tanaka, Yasuhito; Morriseau, Taylor; Wertheim, Joel O. (Frontiers in Microbiology, 2021)
A disproportionate number of Greenland's Inuit population is chronically infected with Hepatitis B virus (HBV; 5-10%). HBV genotypes B and D are most prevalent in the circumpolar Arctic. Here, we report 39 novel HBV/D sequences from individuals residing in southwestern Greenland. We performed phylodynamic analyses with ancient HBV DNA calibrators to investigate the origin and relationship of these taxa to other HBV sequences. We inferred a substitution rate of 1.4x10^{-5} [95\% HPD 8.8x10^{-6}, 2.0x10^{-5}] and a time to the most recent common ancestor of 629 CE [95% HPD 37-1138 CE]. The Greenland taxa form a sister clade to HBV/D2 sequences, specifically New Caledonian and Indigenous Taiwanese sequences. The Greenland sequences share amino acid signatures with subgenotypes D1 and D2, and approximately 97% sequence identity. Our results suggest the classification of these novel sequences does not fit within the current nomenclature. Thus, we propose these taxa be considered a novel quasi-subgenotype.